Clinical features of patients presenting with fever of unknown origin caused by non-tuberculous mycobacterium infection - Liu, Huiting; Zhang, Ting; Wang, Yu; Fan, Hongwei; Huang, Xiaoming; Jiao, Yang (The Journal of Infection in Developing Countries, 2023)
Introduction: Although non-tuberculous mycobacterium (NTM) infection accounts for only a small proportion of fever of unknown origin (FUO) cases, it has become a more common etiology in recent years. Therefore, we reviewed FUO patients with underlying NTM infection to better understand its clinical features. Methodology: The medical records of patients presenting with FUO and diagnosed with NTM infection admitted to Peking Union Medical College Hospital between January 2016 and June 2021 were reviewed. The clinical information of patients whose follow-up data were available were summarized. Specimens submitted for pathogenic identification were processed by mycobacterial culture, acid-fast staining, and mycobacterial nucleic acid detection. IBM SPSS Statistics v22.0 (SPSS, Inc., Chicago, IL, USA) was used for data analysis. Results: Fifty-five FUO patients were diagnosed with NTM infection (55/785; 7.0% of FUO cases). Patients were mostly middle-aged men and had a relatively long disease course. Seven, 29, and 54 patients had previously no respondence to glucocorticoids, immunosuppressants, and multiple antibiotics, respectively; their inflammatory indexes were significantly increased; and there was no obvious risk of immunosuppression in this group, who were likely to be T.SPOT-TB negative (33/41; 80.5%). The most commonly identified NTM was Mycobacterium intracellulare followed by Mycobacterium chelonae/abscessus, Mycobacterium kansasii, and Mycobacterium avium. Conclusions: Microbiological investigations including culture, acid-fast staining, NTM nucleic acid examination, and next-generation sequencing were performed to confirm the diagnosis of NTM in FUO patients. FUO patients should screen for NTM infections so that this important etiology can be recognized, targeted treatments administered early, and outcomes improved.